Optimizing security in Desa Wiyata Tech through Smart Door Lock Implementation: Kutamanah Village, Purwakarta - Liptia Venica; Hauzan Tsaaqif Mushaddaq; Muhammad Rizalul Wahid; Hafiyyan Putra Pratama; Andre Saputra (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Security remains a fundamental concern in many rural educational facilities, where limited infrastructure often leads to increased vulnerability. The “Smart Door Lock” community service program aims to enhance security in public facilities, focusing on SDN 1 Kutamanah in Kutamanah Village, Purwakarta. This initiative is in response to frequent security challenges at the school, highlighting the need for a robust and efficient security solution. The project employs Internet of Things (IoT) technology, installing a Smart Door Lock with anti-theft sensors and a low-power infrared sensor system adapted for limited network areas and energy constraints. The participatory approach involved design, implementation, and user training phases to ensure sustainable operation by the local community and school personnel. Results show improved facility security, especially in high-risk and frequently accessed areas, fulfilling the Sustainable Development Goals (SDGs) of community safety and infrastructure resilience. This technology serves as a model for enhancing security in other public spaces within the village, promoting safety, technological adaptation, digital literacy, and local innovation in rural areas. The project also fosters collaboration between academia, local government, and the community for long-term impact and replicability.